Age-related alterations in the behavioral response to a novel environment in the African turquoise killifish (Nothobranchius furzeri) - Mariën, Valerie; Piskin, Ilayda; Zandecki, Caroline; Van houcke, Jolien; Arckens, Lutgarde (Frontiers in Behavioral Neuroscience, 2024)
The African turquoise killifish (Nothobranchius furzeri) has emerged as a popular model organism for neuroscience research in the last decade. One of the reasons for its popularity is its short lifespan for a vertebrate organism. However, little research has been carried out using killifish in behavioral tests, especially looking at changes in their behavior upon aging. Therefore, we used the open field and the novel tank diving test to unravel killifish locomotion, exploration-related behavior, and behavioral changes over their adult lifespan. The characterization of this behavioral baseline is important for future experiments involving pharmacology to improve the aging phenotype. In this study, two cohorts of fish were used, one cohort was tested in the open field test and one cohort was tested in the novel tank diving test. Each cohort was tested from the age of 6 weeks to the age of 24 weeks and measurements were performed every 3 weeks. In the open field test, we found an increase in the time spent in the center zone from 18 weeks onward, which could indicate altered exploration behavior. However, upon aging, the fish also showed an increased immobility frequency and duration. In addition, after the age of 15 weeks, their locomotion decreased. In the novel tank diving test, we did not observe this aging effect on locomotion or exploration. Killifish spent around 80% of their time in the bottom half of the tank, and we could not observe habituation effects, indicating slow habituation to novel environments. Moreover, we observed that killifish showed homebase behavior in both tests. These homebases are mostly located near the edges of the open field test and at the bottom of the novel tank diving test. Altogether, in the open field test, the largest impact of aging on locomotion and exploration was observed beyond the age of 15 weeks. In the novel tank diving test, no effect of age was found. Therefore, to test the effects of pharmacology on innate behavior, the novel tank test is ideally suited because there is no confounding effect of aging.